INNOVATION IN ARABIC LANGUAGE LEARNING METHODOLOGY: COMBINING TECHNOLOGY AND INTERACTIVE APPROACHES - Khairanis, Retisfa (As-Sulthan Journal of Education, 2024)
This research aims to develop an innovative Arabic learning methodology by integrating technology and interactive approaches to improve effectiveness and student engagement in the learning process. The research method used is a mixed methods approach that includes literature analysis, development of technology-based learning tools, and evaluation through case studies in several educational institutions. Data was collected through classroom observations, interviews, and questionnaires to assess the effectiveness of the implementation of these methods. The results show that the use of technology, such as online-based learning applications and multimedia tools, in combination with interactive approaches such as group discussions, language games, and dialog simulations, can improve students' learning motivation and their communication skills in Arabic. In addition, this method proves to be flexible in various learning contexts, both formal and non-formal. The implications of this study suggest that the incorporation of technology and interactive approaches can be an innovative solution in Arabic language learning, which is relevant to 21st century learning needs. Its contributions include practical recommendations for educators to adopt technology as an integral part of the learning process, as well as providing a basis for further research in the development of more adaptive and effective language learning methodologies.